Some Lexical Uses from Divân of Kâtebi of Neyshâbur - Mohammad Shadrooymanesh; Sara Ghaffari Cherati (مطالعات زبانی و بلاغی)
Shams al-Din Muhammad b. Abdullah Kâtebi of Neyshâbur/Torshiz is a poet and calligrapher of the Timurid era who has been praised by literary historians and biographers for his poetry and creating new meanings. The year of his birth is not mentioned in biographies; we only know that he was born in the second half of the eighth century in the village of Tarq (Rawesh) in Torshiz, Neyshabur. It is known from the references in his divan that in the second half of the eighth and early ninth centuries, when Timur was alive, Kâtebi was a fully-fledged poet. In Neyshabur, he learned literature and calligraphy from the Simi of Neyshabur, who was a master of literature and arts. Katebi became calligrapher, hence the pen name Katebi. The totality of his works consists of ten thousands lines of verse, including odes, tarkibband, tarjiband, mosamat, quatrains, riddles, and Khamseh (five Masnawies). So far Ghazals, from his Divân, and only Majma’-ul-Bahrayn and recently Mohebb-va-Mahbub (or Si-nâmeh), of his Masnawies, have been published. Ketabi has succeeded in contributing to the richness of the Persian language by usinf various forms and sublime themes as well as special attention to figures of speech and the coinage of new words and expressions. In his odes, he imitates Khaghani, and in Masnawi, he is inspired by Nezami. All in all, he is an esoteric and eloquent poet. In an age when good imitation was considered one of the foremost poetic features, his poetry is characterized by close attention to less familiar words and phrases to discover and introduce new and difficult meanings as well as the use of different tropes such as puns, repetitions, alliteration, metonymy, metaphors and conceits, along with imitating and responding to earlier poetry. His works are a repository of ancient and important words, interpretations and word combinations of the Persian language. In this article, after brief sketch of the poet and his works, some of the lexical uses of his poems are introduced based on evidence and verses from his Divân and other texts. These lexical uses fall into two groups: first, those which have not been included in dictionaries, or if included, they are with no evidence or only with evidences from Kâtebi’s poems; second, those which have been explained, discussed and clarified through evidences from Kâtebi’s verse.